SCANNING DAN RESETTING DISTANCE RELAY PADA PENGHANTAR 150 kV KUDUS ARAH JEKULO - Tanzil Ramadhan Aljufri; Bambang Supradono; Luqman Assaffat (MEDIA ELEKTRIKA, 2011)
One unit of P3B Jawa Bali, Central Java and DI Yogyakarta region responsible for operating and maintaining the installation of electric power transmission network in Central Java and Yogyakarta. With the transmission network configuration changes for reasons of consumer needs and for the reliability of the power supply necessary to study the effect of changing the configuration of the coordinated protection system conductor. As happened in the subsystem Kudus-Jekulo-Pati is changing the configuration of the GI Jekulo single phi into a double phi. This change affects the coordination of in the subistem, which overlap in Zone 2 distance in the direction of the GI Kudus-Jekulo to Zone 2 distance relays in GI Jekulo Pati direction, it is known after the scanning process. And to anticipate the problems it is necessary to resetting or setting recalculation distance relay is in the GI Kudus-Jekulo direction, which is expected to resetting, the coordination of protection systems in the susbsistem Kudus-Jekulo-Pati as expected. With better coordination of the protection system conductor protection relay performance became more selective and sustainable electricity distribution maintained the need for electricity can be met in an optimal, effective and efficient. protection systemsKeywords : electric power transmission, protection systems,Distance relay, scanning coordination of protection systems